2005
DOI: 10.1007/s00125-005-0018-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the nitric oxide donor, sodium nitroprusside, on resting leg glucose uptake in patients with type 2 diabetes

Abstract: Aims/hypothesis: Nitric oxide (NO) has been implicated as an important signalling molecule in the contraction-mediated glucose uptake pathway and may represent a novel strategy for blood glucose control. The current study sought to determine whether acute infusion of the NO donor, sodium nitroprusside (SNP), increases leg glucose uptake at rest in patients with type 2 diabetes. Methods: Fifteen male patients with type 2 diabetes (aged 54±4 years, mean±SD) were entered into a randomised, cross-over design study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 50 publications
0
20
1
1
Order By: Relevance
“…NF-B activation also may induce insulin resistance via endothelial dysfunction that arises from altered fatty acid flux, elevated concentrations of asymmetric dimethylarginine, and impaired nitric oxide synthase (NOS) regulation (36 -38). Treatment studies in humans show that antioxidant therapy with vitamin C significantly improves endothelial dysfunction associated with insulin resistance (39) and that NOSmediated endothelial dysfunction in skeletal muscle is associated with impaired nutritive flow redistribution and diminished insulin-mediated and insulinindependent glucose uptake (40,41). We and others have recently shown that biomarkers of endothelial dysfunction are precursors of incident diabetes independent of obesity, inflammation, and other diabetes risk factors (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…NF-B activation also may induce insulin resistance via endothelial dysfunction that arises from altered fatty acid flux, elevated concentrations of asymmetric dimethylarginine, and impaired nitric oxide synthase (NOS) regulation (36 -38). Treatment studies in humans show that antioxidant therapy with vitamin C significantly improves endothelial dysfunction associated with insulin resistance (39) and that NOSmediated endothelial dysfunction in skeletal muscle is associated with impaired nutritive flow redistribution and diminished insulin-mediated and insulinindependent glucose uptake (40,41). We and others have recently shown that biomarkers of endothelial dysfunction are precursors of incident diabetes independent of obesity, inflammation, and other diabetes risk factors (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown a robust increase in peripheral glucose uptake after administration of the NO donor sodium nitroprusside [22]. Based on this work and pilot work, we estimated …”
Section: Statistical Analysesmentioning
confidence: 99%
“…Indeed, it has been shown that infusion of the NO donor sodium nitroprusside improves leg glucose uptake in resting conditions in individuals with and without type 2 diabetes [22,26]. This finding has been attributed to NO-mediated increments in capillary recruitment and nutritive blood flow [22,26].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Nitric Oxide (NO) plays a critical role in skeletal muscle (SkM) physiology [13] and has been implicated in glucose uptake during exercise [49] and in response to insulin [8, 10, 11]. However, the regulatory mechanisms controlling endogenous NO production by nitric oxide synthases (NOSs) in SkM are not fully understood.…”
Section: Introductionmentioning
confidence: 99%